Wellbeing, a complete reference guide Volume II: Wellbeing and the environment - Cooper, Rachel 1953-; Burton, Elizabeth 1967-; Cooper, Cary L. (John Wiley & Sons, 2014)
Part of the six-volume Wellbeing: A Complete Reference Guide, this volume examines the ways in which the built environment can affect and enhance the wellbeing of society. -Explores the effects of environment on wellbeing and provides insight and guidance for designing, creating, or providing environments that improve wellbeing -Looks at the social and health issues surrounding sustainable energy and sustainable communities, and how those connect to concepts of wellbeing -Brings the evidence base for environmental wellbeing into one volume from across disciplines including urban planning, psychology, sociology, healthcare, architecture, and more -Part of the six-volume set Wellbeing: A Complete Reference Guide, which brings together leading research on wellbeing from across the social sciences.
Includes bibliographical references and index. - Description based on title page (Safari, viewed March 18, 2015)
Keywords: Social ecology; Human ecology; Environmental psychology; Well-being; Écologie sociale; Écologie humaine; Psychologie de l'environnement; Bien-être; human ecology; environmental psychology; comfort (sensation); PSYCHOLOGY / General